Challenges of Organizing Mission Surgery in Resource Limited Environments. Issue 4 (June 2015) - Brooke, Sebastian M.; Samson, Thomas D.; Mackay, Donald R.
<x xml:space="preserve">Abstract</x> Abstract Interest in global burden of disease that can be surgically treated is on the rise, and plastic surgeons, with a wide scope of practice, have the tools that make them integral in providing much of the needed surgical support in the world. Since the 1950 s, plastic surgeons have been closely involved in volunteer surgery, and it is through the success and growth of organizations such as Interplast and Operation Smile that we are able to take part in the current paradigm shift to local empowerment and self-sufficiency instead of service delivery alone. This kind of growth started with medical mission work that fostered international partnerships and that remain an important aspect of addressing the unmet surgical burden of disease. Building a mission comprised of an international team of volunteers that travels to a resource-limited environment and provides top-quality surgical care is not without challenges. The aim of this article is to discuss some of these challenges and how they might be overcome.